Aerobic Degradation of Linear Alkylbenzene Sulfonate in Activated Sludge with the Addition of Glucose, KNO3, and KH2PO4 - Arifin, Zainal Syam; Nur Sila Alisi; Ahmad Zaeni (Indonesian Journal of Chemical Science, 2025)
As urban populations grow, the demand for laundry services increases, leading to more detergent waste containing linear alkyl benzene sulfonate (LAS) discharged into the environment. This study investigates the ex-situ degradation of laundry waste in an aerobically activated sludge tank by adding 6 g glucose, 1 g KNO₃, and 0.5 g KH₂PO₄ as nutrient sources. Wastewater samples from two laundry sites were treated with indigenous bacteria from contaminated sludge. The study aimed to assess LAS degradation and reductions in biochemical oxygen demand (BOD) and chemical oxygen demand (COD). LAS levels were monitored over ten days, showing 89.1% and 85.3% degradation efficiencies for the two samples, respectively. BOD decreased from 136.05 to 14.64 mg/L and 140.74 to 13.85 mg/L, while COD dropped from 340.56 to 47.52 mg/L and from 337.91 to 47.49 mg/L. Despite significant BOD reduction, COD levels remained high, indicating the presence of non-biodegradable compounds. The food to microorganisms (F/M) ratio increased over ten days, confirming that activated sludge, with nutrient addition, effectively degrades LAS by over 85%. These results highlight the potential for nutrient-augmented activated sludge systems to manage LAS contamination in laundry wastewater. However, further research is needed to address the persistence of non-biodegradable compounds.